GRÊMIO ESTUDANTIL E PARTICIPAÇÃO DO ESTUDANTE: LIMITES E POSSIBILIDADES PARA O PROCESSO DE EMANCIPAÇÃO EM COMUNIDADES DE PERIFERIAS DA CIDADE DE PONTA GROSSA, PR - Boutin, Aldimara Catarina Brito Delabona (2016)
This paper presents a kind of studies about the students’ councils which actuate inside the state schools from Ponta Grossa, located in the suburb areas. The aim of this research was to analyse these students’ coucils’ limits and possibilities, as they are collegiate instances which represent the schools, for the emancipation process of the communities they are in. The question that has led this research is: How can a students’ council contribute for the emancipation process in this current capitalist society? The object of the research is composed by six students’ councils which actuate in High Schools located in the suburbs and the specific goals which have led all the reflections are: a) Contextualizing the students’ movements which preceded the students’ councils; b) Identifying the goals, being explicit or not, which direct the activities and projects developed by the students’ councils; c) Making the conceptions explicit, the ones that lead the organization of the school performing inside students’ councils from the investigated reality. For the data collection, some semi-structured interviews were used, all answered by students who are the students’ councils’ presidents, selected for the research. Papers like councils’ proceedings and Handbooks and Primers written by SEED-PR and “Instituto Sou da Paz” were also analyzed. The interviews were transcripted, analyzed and classified, considering: the autonomy of the students, who actuate along the councils, the projects which are developed by these councils, the electoral process, the policy emancipation and the human emancipation. As theorist support, the Historical and Dialectical Materialism was used, counting on some authors contribution like: Poermer (1979), Gramsci (1978, 2004), Mandel (1979), Marx (2001, 2010), Tonet (2005, 2010), Sanfelice (1986, 2008), that helped on the dialogues establishment with all the theorist referential and also for the comprehension on how the students movements have configured themselves up to the current structure of the students’ councils. The results from this research show that the policy orientation expressed on the Handbooks and the Primers written by SEED-PR and by “Instituto Sou da Paz” reflects on the projects and activities developed by the councils. It was also possible to note that the manager team gives limits to the students’ participation along the councils, contributing, this way, to inhibit a committed students’ performing when looking for liberating goals. Therefore, this research gives the conclusion the students’ councils which were studied don’t contribute for the emancipation process and that the practice for the policy emancipation is presented in a weak way.